The social influence of teachers and peers on adolescent motivation : a dual perspective - Nasrallah, Rita (Beirut Notre Dame University.Humanities, 2008)
Social variables, like teacher support, praise, peer influence, group affiliation and leadership, exert influence on students' motivation in varying degrees shaping classroom interaction. Teacher support is the most prominent variable, among the other variables, influencing motivation along with praise. Peers, contrary to teachers' perceptions, do not have any significant negative influence on motivation. This is what this research revealed. The study was designed around a literal replication (multiple case study) analyzed through triangulation quantitatively and qualitatively using descriptive statistics, correlation, t-test, One-way analysis of Variance (ANOVA), and Univariate Analysis of Covariance (ANCOVA) in addition to teachers' interviews respectively. The sample consisted of 459 adolescent students drawn from grades 8, 9, 10, 11, 12, and nine of their teachers at three fee-paying private Catholic schools in Keserwan, Lebanon. The results showed that motivation is not exclusively a psychological and/or cognitive construct, but also a socio-cultural one affected by contextual variables like social interaction within a classroom.
: Mémoire
Keywords: Adolescents Les Attitudes et conceptions des enseignants; Adolescents Teachers attitudes and conceptions; Motivation; Motivation